SCHEDULING ANALYSIS BEDUGUL VILLA CONSTRUCTION PROJECT USING PERT AND CPM METHODS - Santoso, Kiswara Agung; Yusnita, Ade Ratna; Pradjaningsih, Agustina (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Scheduling in construction projects is necessary so that the planned time to complete the project can be achieved on time. the methods used in optimizing project scheduling are the Project Evaluation Review Technique (PERT) method and the Critical Path Method (CPM) method. Bedugul Villa is one of the projects that has been carried out with a work contract for 175 calendar days and the scheduling of which will be optimized in this study. The optimal duration for scheduling with the PERT method is to produce an optimal duration of 170 calendar days. The duration is 5 days faster than the existing schedule prepared by the project construction contractor, which is 175 calendar days. The probability of completion of the project is 87.7%. Calculations using the CPM method are 168 calendar days or 7 days earlier than the existing schedule made by the contractor.